Numerical Simulation of the Influence of Non-Uniform ζ Potential on Interfacial Flow - Yu Han; Wei Zhao (Micromachines, 2024)
Zeta potential (ζ potential) is a significant parameter to characterize the electric property of the electric double layer (EDL), which is important at the solid–liquid interface. Non-uniform ζ potential could be developed on a chemically uniform solid–liquid interface due to external flow. However, its influence on the flow has never been concerned. In this investigation, we numerically studied the influence of non-uniform 2D ζ potential on the flow at the solid–liquid interface. It is found, that even without any external electric field and only considering the influence of 2D ζ potential distribution, swirling flow can be generated near EDL, according to the rotational electric volume force. The streamwise vortices, which are important in the turbulent boundary layer, are theoretically predicted in this laminar flow model when considering the 2D distribution of ζ potential, implying the necessity of considering the origin of streamwise vortices of the turbulent boundary layer from the perspective of electrokinetic flow. In addition, the ζ potential distribution can promote the wall shear stress. Therefore, more attention must be paid to shear-sensitivity circumstances, like biomedical, medical devices, and in vivo. We hope that the current investigation can help us to better understand the effect of charge distribution on interfacial flow and provide theoretical guidance for the development of related applications in the future.